Paradigm on Chronic Constipation: Pathophysiology, Diagnostic, and Recent Therapy - Laurentius Aswin Pramono; Ahmad Fauzi; Ari Fahrial Syam; Dadang Makmun (The Indonesian Society for Digestive Endoscopy, 2012)
ABSTRACTChronic constipation is a medical gastrointestinal problem which can degrade patient’s quality of life. So far, the shifting pathophysiologic mechanism to colonic neuropathology has not been supported by diagnostic facility and therapy. Target therapy for chronic constipation related to enteric nervous system is still limited to study. Currently, the discovery of neurotrophin-3 has not shown any significant development needed in daily clinical practice. Until now study related to endoscopic full-thickness biopsy has not been done in human and waiting for its applications in daily practice. Targeted therapy for chronic constipation which is related to enteric nervous system is still limited to study. The discovery of neurotrophin-3, although currently on clinical trial phase II, still not showing any significant contribution in daily clinical practice. New pathophysiologic mechanism shifting the ‘idiopathic’ paradigm or ‘functional’ to colonic neuropathology has not been met with diagnostic modalities and therapy based on this knowledge. Study regarding endoscopic full-thickness biopsy to help revealing this novel mechanism has not been done in human. Henceforth, until now applied studies pertinent to this subject are longing in order for enteric neuron etiology can be firmly established Thus, in the future, translational study is demandingly needed for a firm establishment of diagnostic and therapeutic modalities to its currently evolving pathophysiology. Keywords: chronic constipation, colon, enteric nervous system, neurotophin-3